Retractable roof based on Bricard linkage - Liu, Shiyu (2013)
This project is to design and build a suitable mechanism for the application as a retractable roof through studying and modifying the characteristics of threefold-symmetric Bricard Linkages. [1st Award]-[Peer Assessment Review]